A comprehensive evaluation of the integrated photocatalytic-fixed bed bioreactor system for the treatment of Acid Blue 113 dye - Tiwari H.; Sonwani R.K.; Singh R.S. (My University, 2025)
This work investigated the performance of the integrated system (i.e., a Photocatalytic reactor followed by a Fixed bed bioreactor (PC-FBR)) for the degradation of complex Acid Blue 113 from wastewater. Initially, a Photocatalytic reactor was employed to improve the biodegradability index (i.e., BOD/COD) of wastewater from 0.21 ± 0.0062 to 0.395 ± 0.0058. The preliminary photocatalytic oxidation study revealed a maximum of 86.42 ± 0.33 % dye removal at TiO2 loading of 1.5 g/L and an initial concentration of 50 mg/L of AB 113. An integrated reactor system significantly achieved a maximum of 92 ± 2.6 % of dye removal efficiency under a retention time of 120 hr. The stand-alone FBR dye shock loading study suggested that the reactor system was reasonably able to further restore its degradation efficiency. Langmuir–Hinshelwood kinetic model, Monod model, and Andrew-Haldane model were fitted. The bacterial toxicity assessment was carried out using the Pseudomonas fluorescens. © 2022 Elsevier Ltd